Apakah Belanja Modal dan Belanja Sosial Meningkatkan Pertumbuhan Ekonomi? Bukti Data Panel di Indonesia - Asnawi (Jurnal EMT KITA, 2022)
This study analyzes the effect of capital and social spending on regional economic growth in Indonesia. Using panel data from 24 provinces during the period 2005-2018, the data were analyzed using a panel regression econometric tool with a fixed effect approach. The study pointed out that capital and social spending can significantly increase economic growth. The greater the realization of the local government budget for these two expenditures, the higher the economic growth.